Genome editing using CRISPR/ Cas9 system: a practical guide - A. G. Menzorov; V. A. Lukyanchikova; A. N. Korablev; I. A. Serova; V. S. Fishman (Вавиловский журнал генетики и селекции)
Over the past few years, the CRISPR/Cas techniques have become a revolution in genome editing. Since the original paper on CRIPSR/Cas9 genome editing, researches have proposed numerous modifications of the key components of the CRISPR/Cas9 system to make it extremely efficient. Nowadays, CRISPR/Cas systems can be used not only to modify genomes, but also to control expression levels of defined genes, visualize loci of interest in the space of living cell nuclei, change methylation status of mammalian CpG sites, and to serve many other purposes. Due to an extremely high efficacy and ease of usage, the CRISPR/ Cas system has been employed in a large number of studies in various areas of biology and biotechnology. We have recently published a review describing various CRISPR/Cas systems, mechanisms of their functioning, and applications of the techniques in details. Despite the broad range of potential applications of CRISPR/Cas systems, they are mostly used for genome editing. And, however simple the system may be, there is a number of potential pitfalls on the way towards its use in CRISPR/Cas- naïve laboratory settings. In this article, we describe protocols of CRISPR/Cas9 system generation. We start with a short description of theoretical aspects underlying Cas9-mediated genome editing. Next, we describe a step-by-step protocol of guide RNA vector design and assembly, and several ways of qualitative and quantitative evaluations of the system. Finally, we report protocols of genome editing for modification of embryonic stem cells and zygotes.